Training Of Posbindu Cadres In early detection Of Non Communicable Disease: Training Of Posbindu Cadres In Early Detection Of Non Communicable Disease - Kolibu, Febi Kornela; Maino, Irny; Tewal, Florensia; Asriffudin, Afnal (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
Indonesia is experiencing problems in the health sector, including increasing cases of non-communicable diseases. Non-communicable diseases occur due to various risk factors, such as smoking habits, drinking alcohol, rarely eating fruit and vegetables, rarely doing physical activity, consuming excess sugar and salt. The Indonesian government has launched the Integrated Development Post (Posbindu) program for non-communicable diseases as a concrete form of controlling non-communicable diseases. The Tempok Selatan Village Government has established Posbindu but in its implementation it has not been actively implemented, cadres only carry out posyandu for the elderly. The aim of implementing the activity is to provide training for Posbindu cadres to increase the knowledge and activeness of Posbindu cadres in implementing Posbindu and detecting non-communicable diseases. The method of implementing activities is by providing material, practice, discussion, pre-test and post-test. The results of activities for Cadre knowledge during the pre-test were in the good category, only 50% and after the pre-test it increased to 100%. In the skills of carrying out examinations, measurements and counseling there is an increase in skills. In conclusion, there was an increase in cadres' knowledge and skills after  training. ABSTRAK Indonesia mengalami permasalahan dalam bidang kesehatan diantaranya peningkatan kasus penyakit tidak menular. Penyakit tidak menular terjadi   akibat   berbagai   faktor risiko,  seperti kebiasaan merokok, kebiasaan minum alkohol, jarang makan buah dan sayur, jarang   melakukan   aktivitas   fisik,   konsumsi gula   dan   garam   berlebih. Pemerintah Indonesia telah mencanangkan  program Pos  Binaan  Terpadu (Posbindu) penyakit tidak menular sebagai  wujud nyata  bentuk pengendalian penyakit tidak menular. Pemerintah Desa Tempok Selatan telah membentuk Posbindu tapi dalam pelaksanaannya belum aktif dilaksanakan, kader hanya melaksanakan posyandu Lanjut usia. Tujuan pelaksanaan kegiatan adalah memberikan pelatihan bagi kader Posbindu untuk meningkatkan pengetahuan dan keaktifan Kader Posbindu dalam melaksanakan Posbindu dan mendeteksi penyakit tidak menular. Metode pelaksanaan kegiatan adalah dengan memberikan materi, Praktek, diskusi, pre test dan post test. Hasil kegiatan untuk pengetahuan Kader pada saat pre test kategori baik hanya 50% dan sesudah pre meningkat menjadi 100%. Dalam ketrampilan melakukan pemeriksaan, pengukuran dan konseling terdapat peningkatan ketrampilan. Kesimpulan, terjadi peningkatan pengetahuan dan ketrampilan Kader setelah mendapatkan pelatihan.